Use of Prazosin for Pediatric Post-Traumatic Stress Disorder With Nightmares and/or Sleep Disorder: Case Series of 18 Patients Prospectively Assessed - Ferrafiat, Vladimir; Soleimani, Maryam; Chaumette, Boris; Martinez, Audrey; Guilé, Jean-Marc; Keeshin, Brooks; Gerardin, Priscille (Frontiers in Psychiatry, 2020)
Objectives Few studies have investigated pharmacologic treatment for pediatric post-traumatic stress disorder (PTSD). Prazosin, an alpha-1 adrenergic receptor antagonist, has been studied and demonstrated to be efficacious in an adult population for PTSD related sleep disturbances, however, in the pediatric population, data is limited to case reports and retrospective case series. This study prospectively assessed the safety and effects of Prazosin on PTSD symptoms in a pediatric sample. Methods Since 2016, 18 patients with PSTD under the age of 15 admitted in a child and adolescent psychiatric unit were challenged with prazosin as part of a treatment protocol. PTSD symptoms and adverse effects were collected weekly and prospectively assessed each month with validated clinical scales. All data were retrospectively analyzed. This treatment protocol and the evaluation of clinical data were approved by our Ethical committee for research on preexisting data at the University Teaching Hospital of Rouen. Results Among the 18 patients (10 girls, 8 boys), 13 (72%) had experienced sexual abuse and 5 (28%) family violence. After one month of treatment with a mean prazosin dose of 2.16 (+/-0.6) mg/day, the CGI-S score significantly decreased from 5.3 (+/-0.9) to 2.9 (+/-0.7) (improvement of 43%). The mean total UCLA-PTSD-RI score significantly decreased 11.4 points (+/-5.4) during the first week and 37.9 (+/-16) during the first month leading to an improvement of 20% and 67% respectively. The improvement was significant irrespective of trauma exposure or sex. No adverse effects were reported except for one patient (hypotension). Conclusion Consistent with prior case reports and retrospective reviews, our retrospective analysis of data prospectively and systematically assessed among 18 patient suggests that prazosin is well-tolerated and associated with improvement in symptoms for pediatric PTSD.